BIMBINGAN DAN PELATIHAN KELOMPOK ANEKA USAHA KEMITRAAN PERORANGAN UKM DI BHASKARA DS. KALISARI KEC.MULYOREJO SURABAYA JAWA TIMUR - rulirianto rulirianto; Ayu Febriyanti Puspitasari; Nurul Hidayatinnisa; Ika Kusumasasti (Jurnal Pengabdian kepada Masyarakat, 2020)
As it is known that knowledge and technology are very necessary and useful in an effort to help improve the quality of life of a nation. Knowledge and technology is not only beneficial for ordinary people but also very beneficial for people engaged in business. There are still many of our brothers and sisters who are less fortunate in the sense of doing business as just opening a business. But they don't have enough knowledge about how they should run their business, it's just product oriented, so it's not well known in the community. Therefore knowledge about marketing is very important as well as Product, Price, Place and Promotion. Products include the quality of how they choose good raw materials and good designs so that they get good results too.Surabaya is a large area and consists of many areas such as North Surabaya, East Surabaya, West Surabaya and South Surabaya. Besides that, it is necessary to introduce the location of the place where they are domiciled. So that many people know where the business is and what kind of business. Whether it's in the form of a group of shops, tailors, loundry or other similar businesses. Therefore, as an effort to improve their quality of life and form of care, it is necessary to provide counseling on how to live better by utilizing limited and basic knowledge and technology. In the end this program has the ultimate goal of improving the quality of life of business owners by means of management improvements in the business it owns.